Identification and characterization of a novel homozygous splice site variant of PATL2 causing female infertility due to oocyte germinal vesicle arrest - Sun, Liwei; Tong, Keya; Liu, Weiwei; Tian, Yin; Yang, Sheng; Zhou, Danni; Liu, Dongyun; Huang, Guoning; Li, Jingyu (Frontiers in Genetics, 2022)
Background: This study aims to describe clinical and diagnostic phenotype and identify pathogenic variants of a female with unknown causes of infertility. Methods: Clinical assessment was performed for the phenotype diagnosis. Whole-exome sequencing (WES) and the followed cDNA-PCR sequencing were applied to identify the pathogenic variant and investigate the potentially aberrant mRNA splicing event. The pathogenicity of the variant was analysed using multiple in silico prediction tools, including the 3D protein remodelling. Quantitative RT-PCR (qRT-PCR) was performed to measure PATL2 mRNA expression in the peripheral blood leukocytes of the proband and controls. Results: The proband was diagnosed with the female infertility due to oocyte germinal vesicle (GV) arrest. A novel homozygous splice site variant of PATL2 (NM_001145112.2, c.871-1G>A), inherited from her asymptomatic heterozygous parents, was detected by WES. Sequencing of cDNA amplification products demonstrated that this variant resulted in the exon 10 skipping and in-frame loss of 54 nucleotides in the PATL2 transcript. Quantitative RT-PCR suggested that the mutant transcript escape the mRNA degradation. Conclusion: We identified a novel pathogenic homozygous splice site of PATL2 (c.871-1G>A) underlying the oocyte GV arrest phenotype and elucidated its molecular mechanism. This study expands the variant spectrum of PATL2 and benefits our understanding of its genotype-phenotype correlations.